Navigating College with Disability and Identity: A Narrative Inquiry on the Lived Experiences of an LGBTQIA+ Student with a Limb Impairment - Cahilog , Don T. (Randwick International of Education and Linguistics Science Journal, 2025)
This qualitative research investigates the real-life experiences of a college student who identifies as both LGBTQIA+ and a person with a limb impairment. The study was conducted in Magsaysay College a community college in the Philippines using narrative inquiry, with Riessman’s (2008) Thematic Narrative Analysis guiding the process. The goal was to understand how the participant manages daily college life, builds their identity, and deals with challenges related to both disability and gender identity. Information was gathered through a personal interview and supported by field notes and observations. From the participant’s story, several important themes came out: emotional strength, discrimination, difficulty with physical access, rejection by peers, family struggles, and the strong desire to be treated equally, not differently. The participant shared how they stay motivated despite judgment from others and explained that they don’t want special treatment, just fairness and understanding. What makes this study different is that it focuses on two identities at the same time, being LGBTQIA+ and having a disability, something not often explored in research, especially in the Philippine setting. The findings highlight the need for schools to improve accessibility, train teachers and staff on inclusion, and build systems that respect every student’s identity. This study hopes to give voice to students with similar experiences and encourage schools to create safer, more welcoming spaces where everyone has the chance to succeed and feel like they belong.